Texts from Mittens : a cat who has an unlimited data plan--and isn't afraid to use it - Bailey, Angie (Harlequin, 2015)
"A series of text message conversations between a snappy, self-absorbed housecat named Mittens and his long-suffering human, a single woman who works away from home during the day. Mittens relentlessly hassles his human all day long, while only taking breaks to watch Judge Judy, hang with his best friend Stumpy, complain about the antics of Drunk Patty the neighbor, ask Grandma for money to buy useless items from QVC, and harass the 'filthy beast' dog, Phil"--Amazon.com.